2017
DOI: 10.3390/rs9080859
|View full text |Cite
|
Sign up to set email alerts
|

Wave Height Estimation from Shadowing Based on the Acquired X-Band Marine Radar Images in Coastal Area

Abstract: Abstract:In this paper, the retrieving significant wave height from X-band marine radar images based on shadow statistics is investigated, since the retrieving accuracy can not be seriously affected by environmental factors and the method has the advantage of without any external reference to calibrate. However, the accuracy of the significant wave height estimated from the radar image acquired at the near-shore area is not ideal. To solve this problem, the effect of water depth is considered in the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In this paper, the influence of surface current is investigated. From the experimental results in [17] and this paper, it can be observed that considering both the wave depth and the surface current can improve the retrieving accuracy of wave height. However, the water depth has a greater effect for improving the retrieving accuracy than the surface current, compared to the experimental result in [17].…”
Section: Shore-based Radar Images and Experimentsmentioning
confidence: 74%
See 4 more Smart Citations
“…In this paper, the influence of surface current is investigated. From the experimental results in [17] and this paper, it can be observed that considering both the wave depth and the surface current can improve the retrieving accuracy of wave height. However, the water depth has a greater effect for improving the retrieving accuracy than the surface current, compared to the experimental result in [17].…”
Section: Shore-based Radar Images and Experimentsmentioning
confidence: 74%
“…From the experimental results in [17] and this paper, it can be observed that considering both the wave depth and the surface current can improve the retrieving accuracy of wave height. However, the water depth has a greater effect for improving the retrieving accuracy than the surface current, compared to the experimental result in [17]. The reason is that the observation area of the collected radar belongs to the shallow water area and the retrieving accuracy is greatly affected by water depth.…”
Section: Shore-based Radar Images and Experimentsmentioning
confidence: 74%
See 3 more Smart Citations